PEMAKAIAN UNGKAPAN MAKIAN DALAM BAHASA INGGRIS DALAM MEREAKSI COVER LAGU DALAM PERMAINAN GITAR ALIP BA TA DI YOUTUBE - Nurprihatina Hasan; Andriani Andriani (Universitas Khairun, 2022)
This study aims to classify the forms and functions of English swear words used by the reactors in reacting to Alip's guitar playing in covering western songs or songs from Indonesia and to describe students' perceptions of the English swear words associated with the Cross Culture Understanding (CCU) course material. Data on English swear expressions were obtained through YouTube videos while data on students’ perceptions of English swear words were obtained through a google form. The findings show that the English swear words used by the reactors are generally in the form of the expression 'Fucking' as an adjective and serves to express surprise or praise and as an intensifier to reinforce or emphasize. Although only a small percentage (21.7%) of 23 respondents saw Alip Ba Ta's guitar playing and the reactions of the reactors in the song cover by Alip Ba Ta's guitar it turned out that more than 52% of 23 respondents had used swear words both in English and in Indonesian or in local language. More than 63% of the respondents strongly agree (18.2%) and agree (45.5%) that English swear words need to be included in the CCU course material for a number of reasons, such as to better understand the actual types of swearing with the right meanings, to increase students' knowledge about the use of swear language in various cultures between countries, and to add insights.